Aortic valve neocuspidization using autologous pericardium compared to surgical aortic valve replacement. Issue 10 (23rd July 2022) - Boehm, Johannes; Vitanova, Keti; Prinzing, Anatol; Krane, Markus; Lange, Rüdiger
Abstract: Introduction: Aortic valve neocuspidization (AVNeo) for trileaflet aortic valve reconstruction using autologous pericardium (Ozaki procedure) depicts an encouraging new technique for the surgical treatment of aortic valve pathologies. The current study analyzes the early hemodynamic outcome of AVneo compared with surgical aortic valve replacement (SAVR) using the Abbott/St. Jude Trifecta aortic valve biological prostheses. Methods: All patients who underwent either AVNeo or SAVR between March 2017 and April 2020 were included. Exclusion criteria were emergency cases, endocarditis, redo‐ or additional root procedures. Main endpoints were differences between the two groups in terms of the effective orifice area (EOA) and the effective orifice area index (EOAI) at discharge. Results: During the study period, 105 AVNeo patients and 458 SAVR patients met the inclusion criteria. EOA was significantly higher in the AVNeo group (2.4 cm 2 ± 0.8 vs. 2.1 cm 2 /m 2 ± 0.6 in the SAVR group, respectively; p < .001). Multiple regression analysis, including AVNeo, annulus size, bicuspid valve, preoperative stenosis, left ventricular ejection fraction (LVEF), and diastolic diameter (LVEDD) found two factors, which favor larger EOA: Annulus size ( p < .0001) and AVneo ( p = .005). EOAI was significantly higher in the AVNeo group (1.23 ± 0.4 vs. 1.02 cm 2 /m 2 ± 0.3, respectively; p < .001). Multiple regression analysis for EOAI showed effects for AVneo ( p = .005) and bicuspid valve ( p = .029). Mean pressure gradients (MPG) were lower in the AVNeo group than in the SAVR group (AVNeo: MPG = 8.0 mmHg ± 3.6 vs. SAVR: MPG = 8.3 mmHg ± 3.6), but this finding did not reach statistical significance ( p = .091). Conclusions: AVNeo shows significantly larger EOA and EOAI compared to SAVR using the Abbott/St. Jude Trifecta aortic valve biological prostheses.